Is Britain a force for good? Investigating British citizens' narrative understanding of war. Issue 1 (2nd January 2017) - Colley, Thomas
Abstract: It is commonly assumed in the foreign policy literature that narratives are uniquely persuasive and thus integral to obtaining public support for war. Yet, empirical research on "strategic narrative" is often vague on both the concept of narrative and how it persuades. Moreover, the stories publics use to interpret war are rarely examined. This paper offers a novel approach to studying "from the ground up" the war stories of individual British citizens. It examines public interpretations of war through emplotment: the way people select and link events to create a coherent story. Examining the wars people include and those they silence, it illustrates how a diverse range of citizens morally evaluates Britain's military role, be it as a Force for Good, a Force for Ill or a country Learning from its Mistakes . In doing so, the paper offers an alternative methodological approach to studying how individual citizens understand war.